Effects of acetamiprid on Lipaphis pseudobrassicae (Hemiptera: Aphididae) resistant and susceptible to the parasitoid Diaeretiella rapae (Hymenoptera: Braconidae, Aphidiinae) - Braga Maia, Jader; de Freitas Silva, Paula; Sampaio, Marcus Vinicius; Custódio de Oliveira, Amanda Rosa; Borges Rosa de Moura, Lohaynne; Almeida Silva, Carolinne (Revista Ceres, 2025)
This study evaluated the relationship between the resistance of Lipaphis pseudobrassicae to the parasitoid Diaeretiella rapae and the effects of the insecticide acetamiprid on the aphid. Four groups of L. pseudobrassicae collected in Uberlândia, MG, were used. The first two were formed by individuals of the same clone (C1), which were resistant (C1R) or susceptible (C1S) to the parasitoid. The third group was formed by resistant individuals to the parasitoid descended from a clone collected in canola (C2R) and the fourth group, from a population collected in a commercial plantation of collard greens (P1). Determination of LD50 was done with three replications of 10 aphids, subjected to dose-response assays, with the application of five concentrations of the insecticide acetamiprid (0.01, 0.1, 1, 10 or 100 ng a.i./aphid) and a control treatment consisting of acetone alone. There was no significant difference in the LD50 of individuals of the same clone, C1R and C1S (0.06 ng a.i./aphid for both clones). C2R had the highest LD50 (0.14 ng a.i./aphid), while P1 had the lowest (0.01 ng a.i./aphid). These results suggest that resistance against the parasitoid is not, therefore, associated with the effects of insecticide on L. pseudobrassicae.